Mutter und Sohn im Briefwechsel : 1917 - 1946 ; [eine Veröffentlichung des Leo Baeck Instituts] - Scholem, Betty; Scholem, Gershom 1897-1982; Shedletzky, Itta 1943- Hrsg; Leo Baeck Institute (Beck, 1989)
Betty Scholem/Gershom Scholem: "Mutter und Sohn im Briefwechsel 1917-1946". C. H. Beck Verlag, München 1989. 579 S., 13 Abb., geb., 58,- DM